2017
DOI: 10.1017/s0007485317000864
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of an extract from non-host plants on physiological characteristics of two major cabbage pests

Abstract: The diamondback moth (Plutella xylostella) and small white cabbage butterfly (Pieris rapae) are the two main serious pests of cruciferous crops (Brassicaceae) that have developed resistance to chemical control methods. In order to avoid such resistance and also the adverse effects of chemical pesticides on the environment, alternative methods have usually been suggested, including the use of plant enzyme inhibitors. Here, the inhibitory effects of proteinaceous inhibitors extracted from wheat, canola, sesame, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Similar to the results reported by Datta et al (2019) in tobacco cutworm (Spodoptera litura) caterpillars with Greater galangal (Alpinia galanga) extracts, we found that M. sexta larvae fed on purple corn pericarp extract-containing diet had lower mass and mass gain in early larval stages ( Figure S4A,B and Figure 5A,B) [68]. The low mass and mass gain might be due to either the negative impact of pericarp extract ingested by them through diet or its antifeedant properties [2,[70][71][72][73][74]. To confirm this, we did a no choice (on/off) and a choice assay using Ethovision behavior tracking system.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to the results reported by Datta et al (2019) in tobacco cutworm (Spodoptera litura) caterpillars with Greater galangal (Alpinia galanga) extracts, we found that M. sexta larvae fed on purple corn pericarp extract-containing diet had lower mass and mass gain in early larval stages ( Figure S4A,B and Figure 5A,B) [68]. The low mass and mass gain might be due to either the negative impact of pericarp extract ingested by them through diet or its antifeedant properties [2,[70][71][72][73][74]. To confirm this, we did a no choice (on/off) and a choice assay using Ethovision behavior tracking system.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, artificial induction of defense in oilseed rape plants reduced the survivorship of immature stages of P. xylostella . Probably, the reduction in the survival rate of P. xylostella was because of the increase of inhibitor level in treated plants that affect the feeding, growth, and survival of the immature ( Dastranj et al, 2017 ). Also, inducers are responsible for producing certain secondary metabolites which decrease the survival of herbivores ( Thaler et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides glucosinolate, other secondary metabolites and digestive enzyme inhibitors might have changed and influenced the r of P. xylostella ; as its correlation is shown in Table 4 . Dastranj et al (2017) reported that plant inhibitors reduced survival and delayed growth and development of the P. xylostella larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pieris rapae, one of the major pests of cabbage, has developed resistance to chemical control, so it is one of the most serious and difficult pests to control (Dastranj et al, 2017). Natural pesticides have a number of advantages over synthetic pesticides; they are biodegradable and tend to cause minimal harm to humans, livestock, and wildlife (Benelli, 2016).…”
Section: Introductionmentioning
confidence: 99%